Thermal neutron–induced γ-ray background in 124Sn. (April 2020) - Gupta, G.; Krishnamoorthy, H.; Garai, A.; Mazumdar, A.; Nanal, V.; Shrivastava, A.; Pillay, R.G.
Abstract: The thermal neutron-induced gamma-ray background in 124 Sn is investigated in connection with neutrinoless double beta decay (0 ν β β ) studies in 124 Sn. For this purpose, a 99.26 % enriched 124 Sn sample was irradiated with a thermal neutron fluence of 3 × 10 15 /cm 2 in the Dhruva reactor at the Bhabha Atomic Research Centre, Mumbai. The gamma ray spectra of the irradiated sample were measured in a low background counting setup to study both long-lived and short-lived activities. The present data give an independent measurement of the half-life of 125 Sn*( 3 2 + ) and 125 Sn( 11 2 − ) as 10.01(8) min and 9.63(2) d, respectively. The impact of the observed high-energy gamma rays and the residual activity due to 125 Sb, on the background in the region of interest around the Q β β value of 124 Sn ( ~ 2.291 MeV) is discussed. Highlights: impact of gamma-ray background due to thermal neutron capture in 124 Sn for the region of interest around Qββ ( 124 Sn). The measured background due to gamma rays from 124 Sn (n, γ) in the Qββ ( 124 Sn) region, is found to be consitent with simulation. The present data give an independent measurment of the half-lives of 125 Sn*( 3 2 + ) and 125 Sn( 11 2 − ).